Should travelers with hypertension adjust their medications when traveling to high altitude? - Luks, A. M. (High Altitude Medicine & Biology, 2009)
When advising travelers to high altitude, clinicians should consider how their patient's underlying medical conditions may be affected by the high altitude and whether changes are necessary in their medical regimen. Given the high prevalence of hypertension in the general population, it is a common medical condition that is often considered in this regard. Little information exists, however, to guide the management of this condition at high altitude. This review considers the available data regarding systemic blood pressure responses and the risks of worsening blood pressure control at high altitude and which antihypertensive medications are more effective for blood pressure control in this environment. The available evidence suggests blood pressure rises to a modest extent in patients with mild to moderate hypertension upon acute ascent to high altitude, but there is no clear evidence of an increased risk of complications due to these increased pressures. There is, however, marked interindividual variability in blood pressure responses at altitude; as a result, patients with poorly controlled or very labile hypertension should monitor their blood pressure upon ascent to high altitude and travel with a plan for altering their medical regimen in the event marked or symptomatic blood pressure elevations occur.